2005
DOI: 10.1038/nsmb976
|View full text |Cite
|
Sign up to set email alerts
|

Evolution from DNA to RNA recognition by the bI3 LAGLIDADG maturase

Abstract: LAGLIDADG endonucleases bind across adjacent major grooves via a saddle-shaped surface and catalyze DNA cleavage. Some LAGLIDADG proteins, called maturases, facilitate splicing by group I introns, raising the issue of how a DNA-binding protein and an RNA have evolved to function together. In this report, crystallographic analysis shows that the global architecture of the bI3 maturase is unchanged from its DNA-binding homologs; in contrast, the endonuclease active site, dispensable for splicing facilitation, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…In meiotic crosses this can lead to super-Mendelian inheritance of the LHEG/intron sequence. Some LHEases have been shown to function as maturases and promote the splicing of their host group I intron and occasionally related introns (Lazowska et al 1989;Ho et al 1997;Ho and Waring 1999;Bassi et al 2002;Bassi and Weeks 2003;Belfort 2003;Longo et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In meiotic crosses this can lead to super-Mendelian inheritance of the LHEG/intron sequence. Some LHEases have been shown to function as maturases and promote the splicing of their host group I intron and occasionally related introns (Lazowska et al 1989;Ho et al 1997;Ho and Waring 1999;Bassi et al 2002;Bassi and Weeks 2003;Belfort 2003;Longo et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we purified the LAGLIDADG protein encoded by a group II intron and submitted it to biochemical assays in order to determine (1) if it is required to assist the group II ribozyme in splicing; that is, it acts as a maturase, as has been seen for several LHEases associated with group I introns (Ho and Waring 1999;Bassi et al 2002;Longo et al 2005); and (2) if it has DNA cleavage activity, and, if that is the case, whether its cleavage site is situated at the proximity of the intron IS, in keeping with the possibility that the intron is actually mobilized by the LHEG.…”
Section: Group II Introns With Lhegsmentioning
confidence: 99%
“…Finally, self-splicing introns typically possess helical domains, junctions and loops that have optimal lengths, as first inferred from modeling studies (e.g., 12 base pairs are preferred between the GÁU pair in P1 and the loop L2) (Michel and Westhof 1990). Introns with longer helices and loops may be more prone to misfolding and hence more likely to require a protein for activity (Akins and Lambowitz 1987;Weeks and Cech 1995;Goddard and Burt 1999;Webb et al 2001;Longo et al 2005), yet the thresholds determining such optimal lengths are not known. As a consequence, many basic questions concerning the self-splicing ability of group I introns, the optimal conditions that support catalysis, and the roles of protein facilitators remain barely addressed.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that a close relative of I-AniI, the bi3 maturase from yeast, binds an RNA containing only the P4-P6 and P5ab domains of the mt COB gene (Longo et al 2005). In contrast, I-AniI is incapable of binding the comparable, isolated A.n.…”
Section: Not All Maturases Are Alikementioning
confidence: 99%
“…I-AniI appears unique in this regard, as other group I intron protein cofactors do not require P1-P2 structures for high-affinity binding, and in such cases splicing can be slow relative to the rate of protein binding (Saldanha et al 1995;Webb and Weeks 2001;Longo et al 2005). For example, binding by the Neurospora crassa mt tyrosyl tRNA synthetase protein results in stable, nonnative complexes that require an RNA helicase protein for native complex formation in vivo (Mohr et al 2002).…”
mentioning
confidence: 99%